2021
DOI: 10.1037/pas0000999
|View full text |Cite
|
Sign up to set email alerts
|

The Dialectical Behavior Therapy Adherence Coding Scale (DBT ACS): Psychometric properties.

Abstract: The Dialectical Behavior Therapy Adherence Coding Scale (DBT ACS) is an observer-rated measure used to evaluate the extent to which therapists deliver individual and group DBT with adherence to the manual. Despite its frequent use in clinical trials of DBT, relatively little is known about its psychometric properties. The present study utilized data from six clinical trials conducted in research and community settings with a variety of patient populations. Across these studies, the DBT ACS was used to code a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…The current study focuses on participants enrolled prior to the global pandemic (i.e., between October 2017 and January 2020). (Harned, Korslund, Schmidt, & Gallop, 2021) was used to code randomly selected DBT skills group sessions for adherence and all scored sessions were deemed adherent. Participants randomized to the DBT condition completed, on average, 30 weekly sessions over the course of a year (63% of the 48-week treatment protocol), consistent with treatment compliance in seminal RCTs demonstrating the efficacy of DBT (Linehan et al, 2006;Lynch, Trost, Salsman, & Linehan, 2007).…”
Section: Randomization and Treatmentmentioning
confidence: 99%
“…The current study focuses on participants enrolled prior to the global pandemic (i.e., between October 2017 and January 2020). (Harned, Korslund, Schmidt, & Gallop, 2021) was used to code randomly selected DBT skills group sessions for adherence and all scored sessions were deemed adherent. Participants randomized to the DBT condition completed, on average, 30 weekly sessions over the course of a year (63% of the 48-week treatment protocol), consistent with treatment compliance in seminal RCTs demonstrating the efficacy of DBT (Linehan et al, 2006;Lynch, Trost, Salsman, & Linehan, 2007).…”
Section: Randomization and Treatmentmentioning
confidence: 99%
“…In case of emergency, the standard emergency procedures of each center will be followed. Although outside of office hours availability is considered to be an essential element of DBT by some authors [ 113 , 234 ], the link between telephone consultation and outcome in DBT has not been evaluated [ 95 , 235 ]. There is some preliminary support for the importance of telephone consultation [ 236 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of competence ratings may threaten the validity of our results [ 109 ]. Moreover, treatment adherence will be assessed by trained master psychology students, whereas for DBT, adherence ratings by reliably trained therapists are considered the gold standard [ 240 , 241 ]. However, students will receive a training from experienced therapists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in an RCT of DBT for women with BPD, posttraumatic stress disorder (PTSD), and recent SIB, Harned et al (2014) found that lower therapist adherence was related to patients requesting to be reassigned to a new therapist. Of note, these studies were comprised of relatively small samples ( n ’s = 7–26) and only one study (Harned et al, 2014) used the DBT Adherence Coding Scale (DBT ACS; Linehan & Korslund, 2003), the only measure that has been found to be reliable and valid in assessing adherence to DBT (Harned, Korslund, et al, 2021).…”
mentioning
confidence: 99%